INNOVATIVE AND INVESTMENT COMPONENT OF ENTERPRISE DEVELOPMENT MANAGEMENT IN CONDITIONS OF TRANSPARENCY AND CONVERGENCE - LEPEYKO, Tetiana; VOLIKOV, Volodymyr; GASIMZADE, Malik (Herald of Khmelnytskyi National University. Economic sciences, 2023)
In today's conditions, the rapid pace of technological development and changes in consumer requirements leave enterprises with the requirements of constant innovative activity. Carrying out innovations allows enterprises to maintain competitive advantages, attract new customers, and develop in domestic and foreign markets.The article aims to study the features of the innovation-investment component of enterprise development management in modern conditions of transparency and convergence.It was noted that innovation and investment processes as drivers of enterprise development are complex, multi-stage, and essential for achieving success in dynamic market conditions. It was found that transparency as a component of business policy guarantees that interested parties have access to relevant information about the company's activities and results, which builds trust and reliability. At the same time, convergence involves the integration of different technologies and approaches, which can lead to synergies and new growth opportunities. By considering these factors in their management approach, businesses can improve decision-making, attract investment, and drive sustainable development.The advantages and risks associated with the enterprise's organization of innovation and investment processes in conditions of transparency and convergence are determined. An analysis of the organizational conditions for constructing the innovation-investment subsystem of enterprise development management (elements, principles, connection with transparency, and convergence) was carried out. An analysis of the relationship between the elements of the innovation-investment subsystem of enterprise development management in modern conditions has been carried out.The considered perspectives demonstrate the importance and potential of innovation and investment processes at Ukrainian enterprises based on a transparent model of behavior in the modern business environment, in particular, considering the post-war recovery of the economy, which must be taken into account in the context of convergence both regionally and internationally.
Keywords: innovation; investment processes; development management; enterprise; social responsibility; transparency; target market; convergence; strategy; development